A Comparison of the Dexamethasone Implant (Ozurdex®) and Inferior Fornix-Based Sub-Tenon Triamcinolone Acetonide for Treatment of Inflammatory Ocular Diseases. (17th February 2019) - Errera, Marie-Hélène; Westcott, Mark; Benesty, Jonathan; Falah, Sabrina; Smadja, Jérôme; Orès, Raphaëlle; Pratas, Ana C.; Sedira, Neila; Bensemlali, Amine; Héron, Emmanuel; Goldschmidt, Pablo; Bodaghi, Bahram; et al.
ABSTRACT: Purpose : To evaluate the efficacy and safety of dexamethasone (DEX) implant compared with inferior fornix-based sub-Tenon triamcinolone injection (PSTA) for treatment of uveitis. Methods : A total of 48 eyes received DEX and 49 eyes received PSTA as the first treatment. Results : A total of 31 eyes were implanted with DEX relapsed (64.5%) after the first injection, while 32 eyes were injected with PSTA as the first treatment relapsed (65.3%). Kaplan–Meier estimated survival to overall relapse after the first injection was a mean 20 months± 3.6 months for DEX (median, 7) and 14 months± 1.9 months (median, 9) for the PSTA ( P = 0.505). Of 49 eyes receiving the PSTA implant as the first treatment, inflammation persisted in 14.3% after the first injection but persisted in none after the DEX injection ( P = 0.005). Conclusions : DEX implantation achieved a higher rate of disease control in the initial 12 weeks postinjection with a relative equivalence in the duration of effect and relapse rates when compared with PSTA.